Physicochemical and microbiological evaluation of artisan cheeses from raw milk and verification of good practices in rural properties in the Taquari Valley-RS (Research, Society and Development, 2022)
The production of artisanal cheese, especially those that retain production aspects culturally passed down through generations, is increasingly valued by consumers, however, the current regulations require good agricultural and food manufacturing practices as essential requirements. With the objective of knowing the tradition of the production of this cheese in the Taquari-RS Valley region, 5 rural properties were visited (coded from nº 1 to 5). In the occasion, the milking of the animals was followed, analyzing the Good Agricultural Practices (GAP) and the Good Manufacturing Practices (GMP) of the cheeses. Samples were collected from the milk used whose physical-chemical analysis showed non-compliance for: titratable acidity 20%, cryoscopic index 40%, betalactam antibiotics 40%, presence of chlorides 20%, anhydrous lactose 20% and non-fatty solids 20%; and somatic cell count (SCC) 40%; the other standards showed conformity.  Cheese samples were collected at 7, 15 and 60 days of aging and analyzed for physicochemical and microbiological characteristics. The average moisture content of the cheeses was 46 to 54.9%, and although the milk refrigeration and storage are being done within the foreseen time/temperature, some of the operations performed need more care, since in the microbiological aspect, 100% of the samples were unfit for consumption due to contamination by Staphylococcus aureus; 60% were not up to the standards for total coliforms. One sample presented levels above the standards established in the legislation for Staphylococcus aureus, total coliforms and Escherichia coli. It was concluded that the good agricultural and cattle raising and manufacturing practices adopted in the rural properties were insufficient, which reflected in the results obtained. Many adaptations are necessary for the artisan cheeses to be in compliance with the Brazilian legislation for the use of raw milk in cheese processing, as well as the production of artisan cheeses.